2009
DOI: 10.1111/j.1468-1331.2009.02690.x
|View full text |Cite
|
Sign up to set email alerts
|

Mirror pattern of cerebral artery atherosclerosis in patients with ischaemic stroke

Abstract: Atherosclerosis in cerebral arteries may develop and progress in a mirror pattern. In patients with cerebral artery atherosclerosis, the occurrence and progression of atherosclerosis in the contralateral cerebral artery should be considered during follow-up examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…1,4,8,23 Cross-sectional associations of WSS with CI have not, to our knowledge, been demonstrated before. Still, 1 study reported a lower mean WSS in the common carotid artery ipsilateral to unilateral ischemic stroke, accompanied by more evident atherosclerotic plaques at the same side.…”
Section: Discussionmentioning
confidence: 92%
“…1,4,8,23 Cross-sectional associations of WSS with CI have not, to our knowledge, been demonstrated before. Still, 1 study reported a lower mean WSS in the common carotid artery ipsilateral to unilateral ischemic stroke, accompanied by more evident atherosclerotic plaques at the same side.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with cardioembolism were excluded when we analyzed the frequency of cerebral artery atherosclerosis and relationships with CAD because nonatherosclerotic steno-occlusive lesions of the cerebral artery by embolism from the heart are occasionally indistinguishable from those of atherosclerosis [26]. The SAS statistics package (version 9.2; SAS Institute Inc., Cary, N.C., USA) was used for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Endovascular treatment also was offered for lesions that were discovered during the pretreatment angiography during the endovascular treatment of a symptomatic intra- or extracranial stenotic lesion. The above mentioned lesions are considered to carry an increased risk of subsequent cerebral ischemia [9, 10]. Failure of previous medical therapy was not a compulsory indication criterion for the endovascular treatment.…”
Section: Methodsmentioning
confidence: 99%